Stage-discharge rating curve of Gomati River (alluvial plain tributary of Ganga river) at Chandwak, northern India - Kumar, Sonu; Singh, Priyanka; Verma, Shashwat; Pal, A.; Singh, Satyendra; Kumar, Narendra; Kar, Ratan; Singh, Munendra (International Journal of Hydrology, 2025)
In the northern part of India, the 900-km long Gomati River drains the central Ganga Alluvial Plain and transports its water and sediments to the Ganga River, one of the world’s largest fluvial system. The basin experiences a humid, sub-tropical climate characterised with the monsoon season of heavy precipitation. In the distal part of the river basin, hydrological data were collected from Maighat gauging station located at Chandwak for the present stage-discharge relationship study. With increasing fresh water demands from the ever growing human population in the Ganga Alluvial Plain, the Gomati River Basin has been facing acute crises of water resources and environmental degradation. Thus, the primary aim of the present study is (1) to analyse the stage-discharge relationship of the Gomati River, to detect its seasonal characteristics and (2) to elucidate the reliable stage-discharge rating curve for water resource management and environmental conservation. Findings of the present study indicated that the stage-discharge relationship displayed better correlation coefficient during the summer (R2=0.9881, N = 23) and the post-monsoon (R2=0.9166, N = 18) seasons than the winter (R2=0.8907, N = 27) and the monsoon (R2=0.8925, N = 36) seasons. The seasonal stage-discharge rating curves are discussed with particular reference to predict the accurate discharge variability for the low-gradient single-channel alluvial river. Based on detailed analysis and goodness-of-fit criteria, the linear stage-discharge rating curve was found to be the best for the Gomati River, and demonstrates good predictive accuracy (R2=0.9712, n = 66) with discharge condition of <250 m3/s. The application of results has a great importance due to practicality in water resource management in the densely populated and the highly agricultured alluvial plain of the Gomati River Basin. This is for the first time that the present hydrological rating curve study, based on the real time-series data, has been conducted so far. It is necessary to advance our understanding of the stage-discharge relationship in future studies under the climate change scenario.